2005
DOI: 10.1016/j.febslet.2005.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric behavior of archaeal prolyl‐tRNA synthetase

Abstract: Archaeal prolyl-tRNA synthetases differ from their bacterial counterparts: they contain an additional domain (about 70 amino acids) appended to the carboxy-terminus and lack an editing domain inserted into the class II catalytic core. Biochemical and structural approaches have generated a wealth of information on amino acid and tRNA specificities for both types of ProRSs, but have left a number of aspects unexplored. We report here that the carboxy-terminal domain of Methanocaldococcus jannaschii ProRS is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…Both of these class I tRNA synthetases are homodimers that catalyze (at least under some conditions), synthesis of approximately 1 mol of aminoacyl adenylate. It has also been shown that the class II M. jannaschii ProRS and E. coli HisRS homodimers rapidly synthesize only 1 mol of aminoacyl adenylate per dimer (51)(52)(53). Our data now extend the half-ofthe-sites reactivity phenomenon to also encompass a homotetrameric enzyme; thus, the phenomenon appears to be generally present in multimeric tRNA synthetases of both classes.…”
Section: Discussionmentioning
confidence: 61%
“…Both of these class I tRNA synthetases are homodimers that catalyze (at least under some conditions), synthesis of approximately 1 mol of aminoacyl adenylate. It has also been shown that the class II M. jannaschii ProRS and E. coli HisRS homodimers rapidly synthesize only 1 mol of aminoacyl adenylate per dimer (51)(52)(53). Our data now extend the half-ofthe-sites reactivity phenomenon to also encompass a homotetrameric enzyme; thus, the phenomenon appears to be generally present in multimeric tRNA synthetases of both classes.…”
Section: Discussionmentioning
confidence: 61%
“…A number of oligomeric aaRS have previously been shown to exhibit activity of half of the sites despite containing multiple, seemingly chemically equivalent active and tRNA-binding sites (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30). The mode of tRNA binding described herein argues that SepSecS may follow the sequential model of allosteric regulation (49).…”
Section: Discussionmentioning
confidence: 86%
“…The TyrRS dimer binds one tRNA Tyr (15) and catalyzes formation of 1 mol of tyrosyl adenylate (16 -20), and tetrameric PheRS (15,21) and SepRS (22) employ two of their four catalytic and tRNA-binding sites at a time. Likewise, class II enzymes, bacterial LysRS-II (23,24), AspRS (25), and HisRS (26) and the archaeal and eukaryotic ProRS (27,28) behave according to the "half of the sites" model. The situation is less clear in the case of PylRS and SerRS.…”
mentioning
confidence: 99%
“…Alternatively, the half-of-the-sites reactivity may arise during tRNA binding to a preexisting symmetric dimer to the highly interdigitating and expansive interface of the two monomers (accounting for 26% of the total surface per monomer), which may form the binding surface for the G37 base and may be constructed in such a way to allow only one tRNA to bind to one subunit or alternatively bind across the dimer interface, leading to the stoichiometry of one tRNA bound per dimer. Half-of-the-sites activity has been previously shown for dimeric and tetrameric aaRSs of both the Rossmann-fold and the non-Rossmann-fold type 17;28;29;43;44;45. The discovery of half-of-the-sites reactivity for TrmD suggests that this phenomenon may be general to multimeric enzymes that operate on tRNA.…”
Section: Discussionmentioning
confidence: 88%